Treatment of Insomnia in the Primary Health Care - Ribeiro, Nelson Ferreira (2016)
Insomnia is one of the most common sleep disorders and one of the main complaints of patients that search for medical care. Insomnia disorder is associated with increased morbidity and mortality from accidents, cardiovascular and psychiatric diseases and it is associated with increased absenteeism and higher healthcare costs. We conducted a survey of clinical guidelines, systematic reviews, meta-analyzes and original studies published between 2010 and May 15 2015, concerning insomnia treatment. Treatment of insomnia can begin by cognitive behavioral therapy, pharmacologic treatment or a combination of both. Cognitive behavioral therapy is considered by several medical societies as the standard treatment of insomnia, and studies prove its effectiveness in treating insomnia with or without comorbidities and long-term maintenance of its effects. This comprises multiple strategies such as stimulus control, sleep restriction, relaxation, cognitive therapy and paradoxical intention. Pharmacologic therapy should be considered in acute situations requiring immediate reduction of symptoms. Hypnotic drugs are indicated when insomnia symptoms assume pathological nature. Sedative antidepressants, although generally used, lack evidence of effectiveness, with the exception of insomnia associated with depressive symptoms or anxiety or substance abuse users. Thus, given the prevalence of insomnia symptoms in primary health care, the family physician must know the best approach to its treatment, either pharmacologic or non-pharmacologic, and referral criteria.